ANALISIS PENGARUH STRATEGI BAURAN PEMASARAN TERHADAP PEMILIHAN MEREK LAPTOP MENGGUNAKAN REGRESI LOGISTIK MULTINOMIAL (Studi Kasus Mahasiswa Universitas Diponegoro) - Himmah, Faiqotul; Wuryandari, Triastuti; Hoyyi, Abdul (Department of Statistics, Faculty of Science and Mathematics, Universitas Diponegoro, 2012)
One of necessity is considered very important in this era is necessity for information. The tools that support necessity of comsumer for information, such as computer that use battery or better known as laptop. Laptop is a product often used by businessman/enterprise and academic actors also the student are no exception. There are many laptop brands that revolve in Indonesia, are the Acer brand, Toshiba, Hp, Axioo, Dell, and the brand in addition to those brands. This research aim to know the effect of marketing mix strategy, which consist of three variable factors: product, price, and promotion to the selection of laptop brand in Diponegoro University students. The sample of research taken by using non probability sampling, that is purposive sampling technique dan accidental sampling technique. Analysis that used is multinomial logistic regression analysis, a regression analysis to solve problems where dependent variable has more than 2 categories with several independent variables. Based on the significance test for the overall model and the wald test for each parameter coefficient, consider that three of the marketing mix variables has a relationship with the selection of laptop brand. The biggest probability estimates for the Acer brand in the group with medium product, high price, and high promotion in the amount of 77.461%. The biggest probability estimates for the Toshiba brand in the group with highproduct, high price, and medium promotion in the amount of 49.239%. The biggest probability estimates for the Hp brand in the group with medium product, medium price, and medium promotion in the amount of 46.074%. The biggest probability estimates for the Axioo-Dell brand in the group with with medium product, medium price, and medium promotion in the amount of 14.764%. The biggest probability estimates for the other brands in the group with medium product, high price, and medium promotion in the amount of 22.134%.